2016
DOI: 10.1074/jbc.m116.716514
|View full text |Cite
|
Sign up to set email alerts
|

Rab5 Isoforms Specifically Regulate Different Modes of Endocytosis in Leishmania

Abstract: Differential functions of Rab5 isoforms in endocytosis are not well characterized. Here, we cloned, expressed, and characterized Rab5a and Rab5b from Leishmania and found that both of them are localized in the early endosome. To understand the role of LdRab5 isoforms in different modes of endocytosis in Leishmania, we generated transgenic parasites overexpressing LdRab5a, LdRab5b, or their dominant-positive (LdRab5a:Q93L and LdRab5b:Q80L) or dominant-negative mutants (LdRab5a: N146I and LdRab5b:N133I). Using L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 65 publications
(79 reference statements)
1
41
0
Order By: Relevance
“…Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44). Thus, it is tempting to speculate that Ldgp63 might exit from ER by Sar1-dependent COPII mediated process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we have shown that Ldgp63 is trafficked via Rab1 dependent conventional secretory pathway in Leishmania (36). Moreover, we have also shown that Leishmania has conserved trafficking pathways like higher eukaryotic cells (37)(38)(39)(40)(41)(42)(43)(44). Thus, it is tempting to speculate that Ldgp63 might exit from ER by Sar1-dependent COPII mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Leishmania promastigotes were transfected with respective constructs by electroporation as described previously (36,40). Finally, positive clones were selected in the presence of G418 antibiotic at an initial concentration of 10 µg/ml and thereafter stably maintained at antibiotic concentration of 50 µg/ml.…”
Section: Overexpression Of Copii Complex Proteins In Leishmaniamentioning
confidence: 99%
See 2 more Smart Citations
“…Both endocytic and secretory trafficking pathways regulated by various Rab GTPases are well conserved in Trypanosomatid parasites1819. We have also characterized role of Rab5 and Rab7 in the endocytic pathway of Leishmania 202122 using hemoglobin endocytosis in the parasite23242526. Similarly, we have found that Rab1 regulates the conventional secretory pathway in Leishmania 27.…”
mentioning
confidence: 70%